PENGARUH KUAT ARUS DAN LUAS PENAMPANG ELEKTRODA TERHADAP PENURUNAN KADAR COD DAN TSS PADA LIMBAH CAIR BATIK MENGGUNAKAN METODE ELEKTROKOAGULASI - Ratna Kartika Dewayani; Haryanto Haryanto (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
Along with the development of the batik industry in Indonesia, the number of batik craftsmen is also increasing. However, there are still many batik industries that dispose of their waste directly into the river without being processed first. Batik liquid waste contains organic materials such as COD, BOD, TSS and heavy metals which are dangerous if disposed of directly into the environment. The method used to overcome COD and TSS contamination in batik waste is the electrocoagulation method. The variations used were the electric current (1A, 3A, 5A, 7A, 10A) and the cross-sectional area of ​​the electrode (3x10 cm; 4x10 cm; 5x10 cm; 6x10 cm; 7x10 cm). The results of this study showed that the highest reduction in COD levels was found in the 10 Amper current strength variable with a plate size of 7x10 cm with a COD value of 264.83 Mg / L or 62.12%. Whereas for TSS, the optimum decrease in TSS levels was the 7 ampere current strength variable with a plate size of 7x10 cm, namely 500 mg / L or 86.21%.